2021
DOI: 10.1002/adsc.202100517
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Radical‐Triggered Trifunctionalizing ipso‐Spirocyclization of Unactivated Alkenes with Vinyl Azides: A Modular Access to Spiroaminal Frameworks

Abstract: We report an example of non‐dearomative trifunctionalizing ipso‐spirocyclization of unactivated alkenes through photoredox‐catalyzed, nitrogen‐radical‐triggered cyclization‐trapping‐translocation‐cyclization cascade, providing a single‐step modular access to spiroaminal frameworks through the sequential formation of one C−C bond and two geminal C−N bonds. The developed protocol utilizes not only internal and terminal olefinic oxime esters, but also olefinic amides as nitrogen radical precursors, and features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…20 The N–O bond of oxime esters can be cleaved to generate iminyl radicals through single-electron reduction with the assistance of photoexcited catalysts, inspiring a range of synthetic applications for oxime esters. 21 In our design, the oxime ester served as the electron acceptor, and thus, the 3,5-bis(trifluoromethyl)benzoyl-substituted oxime ester 1a was selected and expected to exhibit superior performance in single-electron reduction (see ESI Table S1†). Silyl enol ether 2a was employed as the radical acceptor, leading to the formation of the functionalized pyrroline 3aa through a cascade of intramolecular cyclization and intermolecular carbon radical trapping.…”
Section: Resultsmentioning
confidence: 99%
“…20 The N–O bond of oxime esters can be cleaved to generate iminyl radicals through single-electron reduction with the assistance of photoexcited catalysts, inspiring a range of synthetic applications for oxime esters. 21 In our design, the oxime ester served as the electron acceptor, and thus, the 3,5-bis(trifluoromethyl)benzoyl-substituted oxime ester 1a was selected and expected to exhibit superior performance in single-electron reduction (see ESI Table S1†). Silyl enol ether 2a was employed as the radical acceptor, leading to the formation of the functionalized pyrroline 3aa through a cascade of intramolecular cyclization and intermolecular carbon radical trapping.…”
Section: Resultsmentioning
confidence: 99%
“…Now, we envisioned whether 2‐benzyl‐2‐bromocarbonyls could also be employed as 1,2‐diradical C2‐synthons and react with 2‐cyanoaryl acrylamides as both radical acceptors and iminyl radical sources to undergo radical alkene difunctionalization along with a cyano insertion and iminyl radical‐involved 1,6‐HAT‐enabled remote C( sp 3 )−H bond functionalization, providing a novel radical relay protocol for accessing novel N‐heterocycle‐fused quinolinone architectures. As a part of our ongoing research toward the iminyl radical‐involved construction of N‐heterocycles, [8g,12] we herein report a novel photocatalytic [2+2+2] cyclization of 2‐cyanoaryl acrylamides with 2‐benzyl‐2‐bromocarbonyls, providing a mild, facile, and straightforward approach to streamline the assembly of structurally diverse functionalized benzo[1,6]naphthyridinones that are frequently found in natural alkaloids [13] and bioactive molecules [14] (Scheme 1C). Additionally, [2+2+1] cyclization of 2‐cyanoaryl acrylamides using more simple starting material 2‐bromocarbonyls was also realized through this photocatalytic system, providing alternative, mild, and green access to functionalized pyrrolo[3,2‐ c ]‐quinolines that widely exist in many natural products [15] as well as bioactive molecules [16] .…”
Section: Methodsmentioning
confidence: 99%
“…12 Obviously, the cycloaddition of nitrile oxides to pyrrolines has the potential to be a useful tool for the assembly of a tetrahydropyrrolo[1,2- d ]oxadiazole core (Scheme 1c). Our comprehensive literature survey revealed that to date only a limited number of pyrroline and nitrile oxide substrates have been involved in the discussed reaction, 8,9,13 so this method cannot be considered a general one. Therefore, a thorough study of the cycloaddition of nitrile oxides to functionalized Δ 1 -pyrrolines with a special emphasis on structure/selectivity relationships remains an attractive and important task for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%